Keautoritarian Manhaj Ahl al-Sunnah wa al-Jamā`ah: Induk dan Benteng Akidah Ummah: Authoritative Approach of Ahl Al-Sunnah wa al-Jamā`ah: A Fundamental and Bastion of Muslims Faith - Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Ahl al-Sunnah wa al-Jamā`ah (Sunni) is the main denomination held by contemporary Muslims. Among its identities is the firmly belief in the concept of Allah’s attributes. It also places and gathers various groups of ulamÉ’ in various disciplines of recognized sciences. This article aims to explain the aspects of the authority of Ahl al-Sunnah wa al-Jamā`ah, especially in the discipline of faith. The study concludes that this manhaj has a scientific feature in interacting with the religious texts (naÎÎ) while having a precise and clear standard in achieving the truth. Its special feature is also manifested by the aspect of its modesity in balancing the superiority of the revelation with the potential of reason. The maturity of the discourse of Ahl al-Sunnah wa al-Jamā'ah qualified it as the fundamental and bastion of Muslims faith.